Hodnocení finanční situace podniku - Klimeš, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalarska prace se zameruje na financni analyzu a take na analyzu bodu zvratu firmy Avis Autovermietung GmbH v letech 2013 - 2016. Nejdrive v praci bude predstavena samotna spolecnost, pote zhodnoceni jednotlivych vysledku financni analyzy a porovnani s doporucenymi hodnotami v oborovem odvetvi. Prace take obsahuje jednotliva navrhy na zlepseni spolecnosti.

The bachelor s thesis focuses on financial analysis and also break even point of Avis Autovermietung GmbH company in the years 2013 - 2016. First of all introduces company, then evaluation of financial analysis and compares with the recommended values in the branch industry. It contains suggestions for improvements in individual analysis.
Evaluation of the Financial Situation of the Company
Keywords: financni analyza; rozvaha; vykaz zisku aztraty; ukazetele rantability; ukazatele likvidity; zadluzenost; bod zvratu; fixni naklady; variabilni naklady; hospodarsky vysledek; zisk; financial analysis; balance; profit and loss statement; profitability ratios; debt management; break even point; fixed costs; variable costs; economic result; profit